Uncovering Hidden Information within UUM Students' Data Using OLAP - Nur Hani, Zulkifli Abai (2010)
The implementation of online analytical processing (OLAP) in speeding decision making process has increased especially in educational industry. Lots of OLAP and Business Intelligence(BI) products have been commercialized, but its implementation in educational industry should be widen up. This study shows the implementation of OLAP in Universiti Utara Malaysia to discover hidden information within UUM students' data. It discussed techniques of data selection and integration to enable university management analyzed integrated students' data online. Issues that have been discussed include data cleaning techniques to ensure data quality before analysis being done and OLAP cube generation technique using SQL Server Analysis Services. This study also elaborates analysis results using OLAP cube that retrieves data online, direct to the server.